Effect of Sequential Acclimation to Various Carbon Sources on the Proteome of Acetobacter senegalensis LMG 23690T and Its Tolerance to Downstream Process Stresses - Shafiei, Rasoul; Leprince, Pierre; Sombolestani, Atena Sadat; Thonart, Philippe; Delvigne, Frank (Frontiers in Microbiology, 2019)
Acetic acid bacteria are very vulnerable to environmental changes; hence, they should get acclimated to different kinds of stresses when they undergo downstream processing. In the present study, Acetobacter senegalensis, a thermo-tolerant strain, was acclimated sequentially to different carbon sources including glucose (condition Glc), a mixture of glucose and ethanol (condition EtOH) and a mixture of glucose and acetic acid (condition GlcAA). Then, the effects of acclimation on the cell proteome profiles and some phenotypic characteristics such as growth in culture medium containing ethanol, and tolerance to freeze-drying process were evaluated. Based on the obtained results, despite the cells acclimated to Glc or EtOH conditions, 86% of acclimated cells to GlcAA condition were culturable and resumed growth with a short lag phase in a culture medium containing ethanol and acetic acid. Interestingly, if A. senegalensis had been acclimated to condition GlcAA, 92% of cells exhibited active cellular dehydrogenases, and 59% of cells were culturable after freeze-drying process. Proteome profiles comparison by 2D-DiGE and MS analysis, revealed distinct physiological status between cells exposed to different acclimation treatments, possibly explaining the resulting diversity in phenotypic characteristics. Results of proteome analysis by 2D-DiGE also showed similarities between the differentially expressed proteins of acclimated cells to EtOH condition and the proteome of acclimated cells to GlcAA condition. Most of the differentially regulated proteins are involved in metabolism, folding, sorting and degradation processes. In conclusion, acclimation under appropriate sub-lethal conditions can be used as a method to improve cell phenotypic characteristics such as viability, growth under certain conditions, and tolerance to downstream processes.